2020
DOI: 10.21203/rs.3.rs-47861/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Survival of silver diamine fluoride among patients treated in community dental clinics: A naturalistic study

Abstract: Background: Silver diamine fluoride (SDF) is a minimally-invasive preventive services used in the U.S. to avert and arrest caries since 2014. Survival outcomes based in real world delivery settings have not been documented. We analyzed 12-month survival outcomes of SDF applied independently or concurrently with other restorative procedures among a population receiving community dental careMethods: We analyzed data on SDF applications from de-identified dental claims on Oregon Health Plan patients served by Ad… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
0
4
0
1
Order By: Relevance
“…In the short time since it has been used in the US for caries arrest, SDF has already been impactful, for example by lowering the use of general anesthesia in young children by 70% in a large Medicaidfocused network of community clinics. 27 SDF is the focus of the ADA evidence-based guideline on NonRestorative Caries Treatment. 3 The WHO acknowledged SDF's potential to equitably decrease suffering from caries by adding it to its Lists of Essential Medicines (for both children and adults).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the short time since it has been used in the US for caries arrest, SDF has already been impactful, for example by lowering the use of general anesthesia in young children by 70% in a large Medicaidfocused network of community clinics. 27 SDF is the focus of the ADA evidence-based guideline on NonRestorative Caries Treatment. 3 The WHO acknowledged SDF's potential to equitably decrease suffering from caries by adding it to its Lists of Essential Medicines (for both children and adults).…”
Section: Discussionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted January 31, 2023. ; https://doi.org/10.1101/2023.01. 27.23285118 doi: medRxiv preprint NOTE: This preprint reports new research that has not been certified by peer review and should not be used to guide clinical practice.…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 99%
See 1 more Smart Citation
“…Gottlieb found that there is a mutual factor concerning the mechanism of desensitizing hypersensitive dentin and arresting DC (49) , also it might possible to measure the SDF caries arresting action in relation to the desensitizing action since the SDF can occlude the dentinal tubules and gives promising results in treating patients with dentin hypersensitivity (12) .…”
Section: -Desensitize Sensitive Teethmentioning
confidence: 99%
“…27,34 Esta terapia está contraindicada en pacientes que reportan alergia a la Plata, 35 los pacientes deben ser monitoreados de cerca para verificar la detención de todas las lesiones de forma periódica en función de los factores de riesgo; esto, es especialmente importante cuando se aplica a los dientes permanentes. 36,37 El seguimiento idealmente debería incluir un examen radiográfico y el plan de manejo de caries debe incluir control de placa, asesoramiento dietético, 27,38 la combinación de otras modalidades de Flúor para la prevención de caries como barniz F, geles de Flúor, enjuagues de Flúor y pasta de dientes con Flúor; además, de ser posible sellantes según la edad y la situación individual del paciente. 25,39 El seguimiento de grandes lesiones o lesiones en áreas difíciles de limpiar se puede combinar con el uso de restauraciones de ionómero de vidrio o tratamiento restaurador tradicional, según las circunstancias del paciente.…”
Section: Desarrollo De La Revisión Narrativa Fluoruro Diamino De Plata Más Yoduro De Potasio (Sdf+ki)unclassified